KUALITAS PELAYANAN KESEHATAN DI RUMAH SAKIT UMUM DAERAH M. YUNUS BENGKULU - Yusuarsono - (UNIVED PRESS, Universitas Dehasen Bengkulu, 2014)
Based on the preliminary survey I conducted at RSUD M. Yunus Bengkulu, there were a number of patients who complained to the services provided by the inner disease clinic. They were unsatisfied with the readiness of officials in giving services and the irregular schedule for medical check –up. They also complained with the time provided by the officials in giving services, which was too short, i.e. starling from 8.00 to 11.30 west Indonesia time. Indeed, the officials often give services star from 9.00 (one hour delay from the schedule), so that the patients felt that the officials carried out the services unprofessionally. This research aims to describe the quality of services provided by the nurses, doctors, and administrative staff in the clinic of inner disease at M. Yunus hospital, Bengkulu. Samples in this research were selected by using accidental sampling method. The data were collected using questionnaire. The collected data that were then analyzed using descriptive qualitative method. The finding shows that the services provided by both nurses and administrative staff were not satisfying. The medical services provided by the doctors in contras were in good quality.Keywords : quality service of nurses, doctors, and administrators.